Integrative Model of Financial Literacy, Social Entrepreneurship, and Pentahelix Collaboration on MSME Performance - Ratna Damayanti; Raisa Aribatul Hamidah; Kartika Hendra Titisari (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of financial literacy, social entrepreneurship, and Pentahelix collaboration on the performance of MSMEs in Karanganyar Regency, with business innovation as a mediating variable. This study aims to understand how internal and external factors interact to improve the performance and competitiveness of MSMEs in the era of digital economy transformation. Research Methodology: A survey of 382 MSME actors in Ngargoyoso, Karangpandan, and Tawangmangu was conducted. Data were analyzed using SEM-PLS with SmartPLS software, testing the outer model, inner model, and mediation to assess direct and indirect relationships. Results: Financial literacy and social entrepreneurship impact MSME performance, while Pentahelix collaboration does not. All three positively influence innovation, which enhances performance. Innovation mediates the relationship between financial literacy and Pentahelix collaboration, but not social entrepreneurship. Conclusions: This study expands the application of the theory of Resource-Based View and open innovation theories by emphasizing that innovation is a strategic bridge between internal resources and external collaboration in strengthening MSME performance and sustainability. Limitations: This study only covers three sub-districts in Karanganyar Regency; therefore, the generalization of results needs to be done carefully. Contributions: This study provides insights into how financial literacy, social entrepreneurship, and pentahelix collaboration impact MSME performance, with business innovation as a mediator. It extends the Resource-Based View and open innovation theories, offering valuable implications for enhancing MSME competitiveness and sustainability in the digital economy.